Reflecting the Nature of the Prophet Muhammad on the Ethics of Internal Auditors - Rayyes, Fishal (Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to explain the reflection of the characteristics of the Prophet Muhammad on the ethics of internal auditors located in Surabaya. This type of research is qualitative phenomenology to capture problems in internal auditors and reveal the meaning contained in them by understanding deeply the characteristics of the Prophet Muhammad SAW which are actualized in the ethics of internal auditors. The approach that will be used in this research is the case study method. This research is also an activity where exploration must be carried out to identify new information and understand the limited circumstances and want to know in depth and detail of the activities to be carried out. The results of this study found that the characteristics of the Prophet Muhammad SAW, namely shiddiq, amanah, tabligh and fathanah, are contained in the values of the code of ethics for internal auditors located in Surabaya.